Adverse events experienced with intrahospital transfer of critically ill patients: A national survey. Issue 18 (7th May 2021) - Temsah, Mohamad-Hani; Al-Sohime, Fahad; Alhaboob, Ali; Al-Eyadhy, Ayman; Aljamaan, Fadi; Hasan, Gamal; Ali, Salma; Ashri, Ahmed; Nahass, Assalh Ali; Al-Barrak, Rana; Temsah, Omar; Alhasan, Khalid; et al.
Abstract : Abstract: Research that focuses on transfers to and from the intensive care unit (ICU) could highlight important patients' safety issues. This study aims to describe healthcare workers' (HCWs) practices involved in patient transfers to or from the ICU. This cross-sectional study was conducted among HCWs during the Saudi Critical Care Society's annual International Conference, April 2017. Responses were assessed using Likert scales and frequencies. Bivariate analysis was used to evaluate the significance of different indicators. Overall, 312 HCWs participated in this study. Regarding transfer to ICUs, the most frequently reported complications were deterioration in respiratory status (51.4%), followed by deterioration in hemodynamic status (46.5%), and missing clinical information (35.5%). Regarding transfers from ICUs to the general ward, the most commonly reported complications were changes in respiratory status (55.6%), followed by incomplete clinical information (37.9%), and change in hemodynamic conditions (29%). The most-used models for communicating transfers were written documents in electronic health records (69.3%) and verbal communication (62.8%). One-fourth of the respondents were not aware of the Situation, Background, Assessment, Recommendation (SBAR) method of patients' handover. Pearson's test of correlation showed that the HCW's perceived satisfaction with their hospital transfer guidelines showed significant negative correlation with their reported transfer-related complications ( r = −0.27, P < .010). Hemodynamic and respiratory status deterioration is representing significant adverse events among patients transferred to or from the ICU. Factors controlling the perceived satisfaction of HCWs involved in patients, transfer to and from the ICU need to be addressed, focusing on their compliance to the hospital-wide transfer and handover policies. Quality improvement initiatives could improve patient safety to transfer patients to and from the ICU and minimize the associated adverse events. Abstract : Supplemental Digital Content is available in the text